2019
DOI: 10.3390/ijgi8030143
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Remote Sensing-Based Vegetation Water Content in Modeling Lightning-Caused Forest Fire Occurrences

Abstract: In this study, our aim was to model forest fire occurrences caused by lightning using the variable of vegetation water content over six fire-dominant forested natural subregions in Northern Alberta, Canada. We used eight-day composites of surface reflectance data at 500-m spatial resolution, along with historical lightning-caused fire occurrences during the 2005–2016 period, derived from a Moderate Resolution Imaging Spectroradiometer. First, we calculated the normalized difference water index (NDWI) as an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Lightning is also one of the important sources of nitrogen oxides in the atmosphere, and thus the occurrence of lightning has a significant influence on global atmospheric chemistry (Schumann and Huntrieser, ; Murray, ; Tost, ). In addition, the cloud to ground (CG) lightning can cause forest fires, hit people and human facilities, causing properties damage, and casualties (Flannigan and Wotton, ; Krause et al, ; Raga et al, ; Abdollahi et al, ; Holle et al, ). Therefore, research on the response of lightning to various meteorological factors and climate change remains an important research topic (Reeve and Toumi, ; Xiong et al, ; Romps et al, ; Kotroni and Lagouvardos, ; Dewan et al, ; Finney et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Lightning is also one of the important sources of nitrogen oxides in the atmosphere, and thus the occurrence of lightning has a significant influence on global atmospheric chemistry (Schumann and Huntrieser, ; Murray, ; Tost, ). In addition, the cloud to ground (CG) lightning can cause forest fires, hit people and human facilities, causing properties damage, and casualties (Flannigan and Wotton, ; Krause et al, ; Raga et al, ; Abdollahi et al, ; Holle et al, ). Therefore, research on the response of lightning to various meteorological factors and climate change remains an important research topic (Reeve and Toumi, ; Xiong et al, ; Romps et al, ; Kotroni and Lagouvardos, ; Dewan et al, ; Finney et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…of weather-related natural hazards such as fire (forest fires, wildfires etc.) [16][17][18][21][22][23][24][25], flood [26][27][28][29][30][31][32], sea-level rise [33,34], landslide [35][36][37][38][39], land subsidence [40,41], drought [42,43] and erosion [44][45][46].…”
Section: Literature Review and Theoretical Foundationsmentioning
confidence: 99%
“…Despite our RS-based four-day FFDFS showing a promising performance of detecting forest fires, we observed that a small number of fires (i.e., 4.35%) were identified in the low fire danger category. This situation could be improved by integrating other forest fire-related variables in this model, such as topographical parameters (e.g., slope, elevation, and aspect of the landscape) that might have influence on the conditions of vegetation [16,17,35], meteorological variables (e.g., incident solar radiation, precipitation, and wind) [16,17], and vegetation phenology to define water stress in vegetation and the fuel availability for fire occurrences [16,36,37].…”
Section: Quantitative Performance Assessment Of the New Four-day Scale Rs-based Ffdfs Modelmentioning
confidence: 99%